Título Padrão - DAMASCENO-MORAIS, Rubens (Revista de Letras, 2022)
This article aims to bring up the discussion about the concept of third party/Third party from different approaches. In this sense, based on a theoretical undertaking in different fields of studies (textual linguistics, discourse studies, argumentation, rhetoric, philosophy, among others.) we suggest a classification that tries to account, at least summarily, of the meaning of the third party. To this end, we divided this work into three moments: a) dialectical perspective, which sees the third party as an indirect allocator, a mediator and an acting role; b) rhetorical perspective, which sees him as a transcendental audience, an arrow directed to a target, a communicational trope and a judge; and, finally, c) logical perspective, which merely deals with the excluded third. The conclusion reached is that there is still a long way to go for us to understand who and what role this third party plays, a fundamental devouring sphinx. Keywords: Third party. Argumentation. Dialectic. Rhetoric. Logic.